Technology developments in endovascular treatment of intracranial aneurysms. (20th November 2014) - Starke, Robert M; Turk, Aquilla; Ding, Dale; Crowley, Richard W; Liu, Kenneth C; Chalouhi, Nohra; Hasan, David M; Dumont, Aaron S; Jabbour, Pascal; Durst, Christopher R; Turner, Raymond D
Abstract : Advances in the management and endovascular treatment of intracranial aneurysms are progressing at a tremendous rate. Developments in novel imaging technology may improve diagnosis, risk stratification, treatment planning, intraprocedural assessment, and follow-up evaluation. Evolution of devices, including microwires, microcatheters, balloons, stents, and novel scaffolding devices, has greatly expanded the potential to treat difficult aneurysms. Although developments in technology have greatly improved the efficiency and efficacy of treatment of neurovascular disorders, novel devices do not always improve outcomes and may be associated with unique complications. As such, it is paramount to have an in-depth understanding of new devices and the implications of their introduction into clinical practice. This review provides an update on developments in endovascular treatment of intracranial aneurysms.